Analysis of Daily Temperature Extremes Indices in Iraq - أحمد لفته حمد البديري, م.د. (lark, 2021)
Climate change and its effects are among the most important challenges facing a man in the 21st century. The current study dealt with the evaluation of temporal and spatial trends of indicators of daily maximum and minimum temperature extremes in Iraq for the period (1985 - 2020). Using ten indicators to measure thermal extremes based on the data of the European Centre for Weather Forecasts Medium-range (ECMWF) for twelve grid points representing Iraq stations, using (Rho) test, linear regression equation. The results of the study revealed a trend towards an increase in the (TXx, TXn, TNx, TNn) indicators and the highest amount of increase in the (TXn) indicator ) by (0.49) °C per decade, with statistical significance at the annual level, and the northern regions were the most changeable in the mentioned indicators The indicators of cold days and nights (TX10p, TN10p) recorded a decreasing trend, and the highest amount of decrease in the cold days index was (2.6-)  % for the decade. The indicators of hot days and nights (TX90p, TN90p) witnessed an increasing trend with high statistical significance, and the highest amount of increase in the indicator of hot days was by (2.9%) for Decade. As for the indicator of summer days (SU) and tropical nights (TR) also recorded a clear trend towards increase and reached the highest amount of increase in class days by (4.3) days per decade with statistical significance The current results confirm the increase of climatic extremes due to the phenomenon of global warming, and thus . The importance of the results of the study show the future challenges facing Iraq in the coming decades, especially on water resources, food security, human health, and energy consumption, which requires setting appropriate policies to adapt to climate changes and their future effects.
Keywords: indicators of temperature extremes, trend, daily temperatures, climate change, Iraq.